La representación política como drama (A propósito de un ensayo de Francisco Ayala) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
This article is dedicated to explain and analyse some of the similarities between two types of representation: dramatic representation, on one hand, and political representation, on the other. This analysis is carried out from the basis of the short essay “Histrionismo y representación”, published by Francisco Ayala in 1944. Besides, in line with the words of Ayala, there are some reflections about the present and the future of democratic political representation model.
Keywords: Dramatic Representation; Political Representation; Parliament; Fiction